Aplikasi Berita Online Berbasis Android: Studi pada Pemerintah Kabupaten Labuhanbatu - D.Leo Surya Duha; Sumitro Sarkum; Ibnu Rasyid Munthe; Iwan Purnama (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Designing an Android-based News application using UML (Unified Modeling Language) that is implemented using Android Studio, while the Android Application uses PHP and MySQL Programming for the database. The programming used is Android-based programming using a MySQL database for php script creation. The results showed that the Android-based news application as a news data processing process that occurred in Labuhanbatu Regency could be done quickly, efficiently and economically; Then the results also show that processing news data from online media on the application facilitates work processes that can improve agency performance.